Adopting Risk Based Maintenance Strategy of Export Gas Pipeline Using House of Risk: A Proposed Framework - Prijambodo, Moko; Baihaqi, Imam (Institut Teknologi Sepuluh Nopember, 2020)
42â€ SNP-BEM is the biggest buried gas export pipeline belong to PT XYZ and has been operated joinly with PT POMA for duration of 20 years. Until today, this pipe has survived very well from the worst potential failure or risk events such as rupture and leak since all strategic of maintenances are considered as sufficient facing the sources of risk agent, despite still different perceptions are presence among the operators in real application. Nevertheless, following the operation versus times, there is an increasing of potential external threat or risk agents due to the growth of housing, the overlapped operational permit of industrial of non-oil/gas, illegal road crossing which may cause the occurrence of risk events/failures. In 2016, there was a critical incident of the soil movement caused by the excessive load of coalâ€™s stock pile nearby ROW and impacted to the pipe movement about 6 meters in horizontal and 2 meters in vertical and may lead to disastrous. Therefore, a more effective maintenance strategy is to be developed to reduce these risks. Combination of Fish Bone diagram (FBD) and House of Risk (HOR) is selected to identify the sources of risk and to develop more effective risk-based maintenance strategy. Based on the assessment, it is identified (twelve) 12 credible risk agents which contributing to pipeline failures/risk events and (eight) 8 proposed preventive actions to reduce the risk. These proposed actions shall be agreed by all operators as a reference for developing risk-based maintenance strategy.